2023
DOI: 10.3389/fimmu.2023.1103231
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitochondria-bound HK2 in rheumatoid arthritis fibroblast-like synoviocytes

Abstract: BackgroundGlucose metabolism, specifically, hexokinase 2 (HK2), has a critical role in rheumatoid arthritis (RA) fibroblast-like synoviocyte (FLS) phenotype. HK2 localizes not only in the cytosol but also in the mitochondria, where it protects mitochondria against stress. We hypothesize that mitochondria-bound HK2 is a key regulator of RA FLS phenotype.MethodsHK2 localization was evaluated by confocal microscopy after FLS stimulation. RA FLSs were infected with Green fluorescent protein (GFP), full-length (FL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Experimental evidence suggests that invasive FLS exhibit significantly enhanced glucose metabolism, thereby contributing to joint damage in the arthritis model. Key enzymes involved in glycolysis, such as phosphoglycerate kinase, play important roles in promoting an inflammatory environment within joints and synovial hyperplasia during FLS invasion behavior [ 43 45 ]. Recent studies have shown a strong correlation between the synovial expression of IL-34 and factors such as rheumatoid factors, erythrocyte sedimentation rate, CRP, and the progression of arthritis on radiographic imaging [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence suggests that invasive FLS exhibit significantly enhanced glucose metabolism, thereby contributing to joint damage in the arthritis model. Key enzymes involved in glycolysis, such as phosphoglycerate kinase, play important roles in promoting an inflammatory environment within joints and synovial hyperplasia during FLS invasion behavior [ 43 45 ]. Recent studies have shown a strong correlation between the synovial expression of IL-34 and factors such as rheumatoid factors, erythrocyte sedimentation rate, CRP, and the progression of arthritis on radiographic imaging [ 46 ].…”
Section: Discussionmentioning
confidence: 99%